A systematic review of adults’ sitting balance assessments in neurological and neuromuscular conditions - Alammar, Walaa A (Neurosciences (Riyadh), 2020)
OBJECTIVES: To find out new assessment tools for sitting, in patients with neurological and neuromuscular conditions, to be recommended for rehabilitation practice locally in Saudi Arabia and internationally. METHODS: Four databases were used: PubMed, Web of Science, Ovid Medline, and Cochrane. Inclusion criteria were articles published between the years 2009–2019; sitting, not standing or walking; assessment not intervention; published in English and studies on adults only. Exclusion criteria were any assessment that measures the standing/walking ability or has items for that, and studies that include pediatric or adolescent or both. RESULTS: Ten articles met our criteria including 464 patients and divided into 3 main neurological conditions (stroke, SCI, and MS). One assessment (Function in Sitting Test) showed promising potential being implemented with both stroke and multiple sclerosis, Cronbach’s alpha, α were 0.91 and 0.98 indicating high internal consistency. It was used with SCI patients, however, no access was available to include this study in this review. CONCLUSION: This review indicates an extension of what was carried out by previous systematic reviews with neurological conditions. It seems that Function in Sitting Test is the most frequent assessment in this review with multiple neurological conditions (stroke, MS and SCI) with high internal consistency and high quality studies according to available data. However, this review showed that there is an absence of evidence for individuals with brain injury. Further work needs to be carried out to address such groups of patients to extend the choices that clinicians can use in rehabilitation sittings.